1997
DOI: 10.1111/j.1530-0277.1997.tb04448.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of ADH and ALDH Genes among Four Ethnic Groups in China and Effects upon the Risk for Alcoholism

Abstract: The alcohol dehydrogenases (ADHs) and aldehyde dehydrogenases (ALDHs) that metabolize ethanol are polymorphic. Different alleles encode subunits of the enzymes that differ in their rate of metabolizing ethanol. These polymorphisms are distributed differently among populations and have been shown to influence the risk for alcoholism in some Asian populations. We have examined the allele frequencies at the ADH2, ADH3, and ALDH2 loci in four populations from China (Han, Mongolian, Korean, and Elunchun) and in alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(111 citation statements)
references
References 23 publications
7
100
3
1
Order By: Relevance
“…Subsequent studies have also reported reduced rates of the ALDH2*2 allele among alcoholics in Asian populations [15]. ALDH2*2 confers up to a 10-fold reduction in the risk of alcohol dependence, giving it a stronger protective effect than either the ADH1B or ADH1C genes [15].…”
Section: Genes Involved In Alcohol Metabolismmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent studies have also reported reduced rates of the ALDH2*2 allele among alcoholics in Asian populations [15]. ALDH2*2 confers up to a 10-fold reduction in the risk of alcohol dependence, giving it a stronger protective effect than either the ADH1B or ADH1C genes [15].…”
Section: Genes Involved In Alcohol Metabolismmentioning
confidence: 96%
“…The alcohol dehydrogenase (ADH) class I isozymes play the major role in ethanol metabolism, and genetic polymorphisms have been detected in two of these genes, which code for subunits of proteins that, in vitro, have greater enzymatic activity, suggesting faster conversion of ethanol to acetaldehyde in individuals carrying these alleles. A number of studies have reported lower frequencies of both the ADH1B*2 and ADH1C*1 alleles in alcoholics than in nonalcoholics in a variety of East Asian populations [15]. More recently, a study of Jewish men living in Israel found that the ADH1B*2 allele was related to a reduced level of peak weekly alcohol intake [16].…”
Section: Genes Involved In Alcohol Metabolismmentioning
confidence: 97%
“…A high frequency of the ALDH2 gene coding for an inactive enzyme along with a high frequency of the ADH2(2) allele (corresponding to the ADH1B A allele in our study) has been described as an Asian pattern that was observed among Han Chinese, Koreans and Japanese while other Asian populations did not exhibit this pattern (Goedde et al, 1992;Thomasson et al, 1994;Higuchi et al, 1996;Shen et al, 1997;Chen et al, 1999). A recent analysis of multiple SNPs from 52 Native American and 17 Siberian groups confirmed the hypothesis that the Inuit descend from the second of three migration waves from Siberia to the Americas but that half of their genome derives from the first, major migration (Reich et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
“…Among these, a functional relevance of the ADH1C genetic polymorphisms that appear to impact on ethanol metabolism and susceptibility to alcoholism has been reported [7]. Its role in the development of alcohol dependence differs according to ethnicity [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28]. Furthermore, small studies have generated somewhat inconsistent results, especially in populations where the minor allele frequency is low, which would serve to reduce statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…The homodimeric γ 1 /γ 1 enzyme has a 2.5-fold higher maximal velocity of ethanol oxidation compared to the homodimeric γ 2 /γ 2 enzyme [7]. The more common (although present at frequencies of 0.12–0.94 depending on ethnicity), fully functional allele ADH1C * 1 allele that encodes more active enzyme has been associated with reduced risk for alcohol dependence in Asian populations [20]. There are differences in expression of phenotype, in locus heterogeneity, in risk alleles, and in population structure [29].…”
Section: Introductionmentioning
confidence: 99%